Evaluation of finger millet (Eleusine coracana) under irrigated and rainfed conditions as a fooder crop on the Pietersburg Plateau, South Africa - Maenetja, Nurse Pertunia (My University, 2021)
Finger millet (Eleusine coracana) is believed to be adapted to the arid and semi-arid regions, highly tolerant to pests, diseases and drought. It has the potential to produce a high forage biomass with fewer inputs under good production practices. The aim of the study was to evaluate the potential of finger millet as a fodder crop on the Pietersburg Plateau under rainfed and irrigation conditions, planted in rows and broadcast. The study was conducted for two consecutive seasons (2017 and 2018) at the Syferkuil Experimental Farm (SEF), University of Limpopo. Treatments consisted of two watering treatments (irrigation and rainfed) and two planting methods (broadcast and row planting). Seeding rate was 10 kg ha-1 with the inter row spacing of 25 cm. Irrigation had a significant effect on the dry matter production of finger millet (P ≤ 0.05). During 2017 growing season, under rainfed condition, the crop experienced zero production due to low rainfall. The total dry matter production of finger millet under rainfed conditions in 2018 was 3371 kg ha-1 for row planting and 3770 kg ha-1 for broadcasting. The dry matter production of finger millet under irrigation and row planting was 5318 kg ha-1 compared to 3371 kg ha-1 produced under row planting in the rainfed conditions. Broadcasting under irrigation produced 4890 kg ha-1 whereas broadcasting under rainfed conditions yielded 3770 kg ha-1. Planting method had no significant effect on the dry matter production of finger millet (P ≤ 0.05). The total dry matter production in 2017 was 5668 kg ha-1 and 5122 kg ha 1 under row planting and broadcast respectively, 2018 season produced the total dry matter production of 5122 kg ha-1 under row planting and 4892 kg ha-1 under broadcast. Finger millet planted under rainfed in rows had the CP% of 14.76 and 16.87% when broadcasted. In all the treatments CP% was higher than 10%. The ADF% was 33.02% under rainfed conditions and it ranged between 30.99% and 31.53% in 2017 and 2018 for row planting under irrigation. Finger millet can be considered an alternative fodder crop for livestock farmers in the Pietersburg Plateau
Thesis (M.Sc. Agriculture (Pasture Science)) -- University of Limpopo, 2021
Keywords: Broadcast; finger millet; irrigation; rainfed; rows; Eleusine coracana; Dry farming; Ragi